Preparation method of carbon-supported nano zero-valent iron catalytic material based on multi-metal catalysis
By introducing a multi-metal collaborative catalytic system and a special carbon support into nano zero-valent iron catalytic materials, the problem of poor stability of nano zero-valent iron materials is solved, the catalytic activity and stability are significantly improved, and environmental restoration and chemical catalysis are achieved Widely used in the field.
Patent Information
- Application Number
- CN202411594296.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-09
- Publication Date
- 2025-02-18
AI Technical Summary
The existing nano zero-valent iron catalytic materials have problems such as poor stability and easy agglomeration, resulting in room for improvement in their catalytic performance and preparation process.
By introducing a multimetallic collaborative catalytic system and a special carbon support, combined with an optimized preparation process, carbon-supported nano zero-valent iron catalytic material based on multimetallic catalytic is prepared. This method includes the composite of carbon nanofibers and porous graphite as a carbon support, and the synergistic effect of major catalytic metals such as iron, cobalt, nickel and auxiliary metal salts such as molybdenum and tungsten to ensure high quality of the material through a multi-step preparation process.
It significantly improves the catalytic activity and stability of catalytic materials and provides a wide range of application prospects, especially in the fields of environmental restoration and chemical catalysis.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic materials, and in particular to a method for preparing a carbon-supported nanometer zero-valent iron catalytic material based on multi-metal catalysis. Background Art
[0002] With the increasingly severe environmental problems and the increasing demand for efficient catalysts in the chemical industry, the development of new and efficient catalytic materials has become a hot topic in current research. Nano-zero-valent iron has great application potential in many fields due to its high reactivity, but single nano-zero-valent iron has problems such as poor stability and easy agglomeration. Although there are some methods to improve nano-zero-valent iron in the prior art, there is still a lot of room for improvement in catalytic performance, stability and preparation process. Summary of the invention
[0003] The object of the present invention is to provide a method for preparing a carbon-supported nano-zero-valent iron catalytic material based on multi-metal catalysis. The catalytic material prepared by the method has high catalytic activity, good stability and broad application prospects.
[0004] The present invention achieves significant improvement over the prior art by introducing a multi-metal synergistic catalytic system and a special carbon carrier in combination with an optimized preparation process.
[0005] Technical Solution
[0006] A method for preparing a carbon-supported nanometer zero-valent iron catalytic material based on multi-metal catalysis comprises the following steps:
[0007] Step 1: Raw material preparation
[0008] A carbon carrier is selected, wherein the carbon carrier is a composite of carbon nanofibers and porous graphite. The mass ratio of carbon nanofibers to porous graphite is 1:2. At least three metal salts are prepared, including an iron salt as the main catalytic metal, a cobalt salt and a nickel salt that can promote the formation of nano zero-valent iron, and an auxiliary metal salt for enhancing stability and catalytic activity, wherein the auxiliary metal salt is a molybdenum salt or a tungsten salt. The metal salts are mixed in a specific molar ratio, i.e., iron salt: cobalt salt: nickel salt: auxiliary metal salt = 5:2:2:1, and the total molar concentration of the metal salts is 0.1 mol / L-0.5 mol / L.
[0009] Step 2: Carbon carrier pretreatment
[0010] The carbon carrier is immersed in a solution containing a specific concentration of an oxidant, the concentration of the oxidant is 0.1 mol-0.3 mol, the immersion treatment temperature is 40°C-60°C, and the treatment time is 2h-4h. Then it is washed with deionized water until neutral, and then subjected to high-temperature heat treatment in an inert atmosphere, the heat treatment temperature is 400°C-600°C, and the treatment time is 2h-4h, so that the carbon carrier is activated and reaches a preset surface state.
[0011] Step 3: Preparation of multi-metal precursor solution
[0012] The mixed metal salts are dissolved in a mixed solvent consisting of an organic solvent and water, wherein the organic solvent is a mixture of ethylene glycol and glycerol, to form a uniform multi-metal precursor solution.
[0013] Step 4: Impregnation reaction
[0014] The pretreated carbon carrier is immersed in the multi-metal precursor solution and the impregnation reaction is carried out under specific temperature and stirring conditions. The reaction temperature is 60°C-80°C, the stirring speed is 200r / min-500r / min, and the reaction time is 4h-6h, so that the metal ions are fully adsorbed on the carbon carrier.
[0015] Step 5: Restore
[0016] A reducing agent is added to the system after the impregnation reaction. The reducing agent is a mixture of sodium borohydride and sodium citrate. A reduction reaction is carried out at a certain temperature. The temperature of the reduction treatment is 30°C-50°C. The reaction time is 1h-2h. The metal ions are reduced to nano zero-valent metals and loaded on the carbon carrier to form a carbon-supported nano zero-valent iron catalytic material based on multi-metal catalysis.
[0017] Step 6: Post-processing
[0018] The product after reduction treatment is filtered and washed to remove residual reactants and impurities, and then dried at a specific temperature of 80°C-120°C and a drying time of 4h-8h to obtain a pure carbon-supported nano zero-valent iron catalytic material based on multi-metal catalysis.
[0019] Beneficial Effects
[0020] 1. The present invention significantly improves the catalytic activity of the catalytic material by introducing multiple metals to form a synergistic catalytic system. The main catalytic metals such as iron, cobalt, and nickel interact with auxiliary metals such as molybdenum and tungsten to enhance the performance of the material.
[0021] 2. The present invention uses a composite of carbon nanofibers and porous graphite as a carbon carrier, combining the advantages of both, providing a larger specific surface area and a more stable structure for metal loading, and improving the stability of the catalytic material.
[0022] 3. The present invention ensures high-quality preparation of catalytic materials by precisely controlling the parameters of each step, including temperature, time, stirring speed, etc., and using a specific combination of oxidant, organic solvent and reducing agent.
[0023] 4. The catalytic material of the present invention has broad application prospects in the fields of environmental remediation, chemical catalysis, etc., and can effectively solve the demand for high-efficiency catalytic materials in some current fields. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Embodiment 1:
[0026] The present invention provides a method for preparing a carbon-supported nanometer zero-valent iron catalytic material based on multi-metal catalysis, comprising the following steps:
[0027] Step 1: Raw material preparation
[0028] A carbon carrier is selected, and the carbon carrier is a composite of carbon nanofibers and porous graphite. The mass ratio of carbon nanofibers to porous graphite is 1:2. At least three metal salts are prepared, including iron salts as the main catalytic metal, cobalt salts and nickel salts that can promote the formation of nano zero-valent iron, and auxiliary metal salts for enhancing stability and catalytic activity, and the auxiliary metal salts are molybdenum salts or tungsten salts. The metal salts are mixed in a specific molar ratio, that is, iron salt: cobalt salt: nickel salt: auxiliary metal salt = 5:2:2:1, and the total molar concentration of the metal salts is 0.1 mol / L.
[0029] Step 2: Carbon carrier pretreatment
[0030] The carbon carrier is immersed in a solution containing a specific concentration of an oxidant, the oxidant concentration is 0.1 mol, the immersion treatment temperature is 40°C, and the treatment time is 2 hours. It is then washed with deionized water until neutral, and then subjected to high-temperature heat treatment in an inert atmosphere, the heat treatment temperature is 400°C, and the treatment time is 2 hours, so that the carbon carrier is activated and reaches a preset surface state.
[0031] Step 3: Preparation of multi-metal precursor solution
[0032] The mixed metal salts are dissolved in a mixed solvent consisting of an organic solvent and water, wherein the organic solvent is a mixture of ethylene glycol and propylene glycol, to form a uniform multi-metal precursor solution.
[0033] Step 4: Impregnation reaction
[0034] The pretreated carbon carrier is immersed in the multi-metal precursor solution and the impregnation reaction is carried out under specific temperature and stirring conditions. The reaction temperature is 60°C, the stirring speed is 200r / min, and the reaction time is 4h, so that the metal ions are fully adsorbed on the carbon carrier.
[0035] Step 5: Restore
[0036] A reducing agent is added to the system after the impregnation reaction. The reducing agent is a mixture of sodium borohydride and sodium citrate. The reduction reaction is carried out at a certain temperature. The temperature of the reduction treatment is 30°C and the reaction time is 1 hour. The metal ions are reduced to nano zero-valent metals and loaded on the carbon carrier to form a carbon-supported nano zero-valent iron catalytic material based on multi-metal catalysis.
[0037] Step 6: Post-processing
[0038] The product after reduction treatment is filtered and washed to remove residual reactants and impurities, and then dried at a specific temperature of 80°C and 4 hours to obtain a pure carbon-supported nano zero-valent iron catalytic material based on multi-metal catalysis.
[0039] In this embodiment, multi-metal synergistic catalysis: iron salt, cobalt salt, nickel salt are introduced as the main catalytic metals, and molybdenum salt or tungsten salt is used as the auxiliary metal salt to form a multi-metal synergistic catalytic system. The interaction between different metals can significantly improve the catalytic activity of the catalytic material and make the catalytic reaction more efficient.
[0040] Advantages of special carbon carriers: The composite of carbon nanofibers and porous graphite is used as the carbon carrier, which combines the high specific surface area of carbon nanofibers and the good stability and pore structure of porous graphite. This special carbon carrier provides more attachment sites for the loading of metal salts, which is beneficial to improve the catalytic performance of catalytic materials.
[0041] Carbon carrier pretreatment: By soaking the carbon carrier in a solution containing a specific concentration of oxidant, and then performing high-temperature heat treatment under an inert atmosphere, impurities on the surface of the carbon carrier can be removed, the surface of the carbon carrier can be activated, and its stability can be improved. At the same time, this pretreatment method can also make the bond between the carbon carrier and the metal salt more firm, and enhance the stability of the catalytic material.
[0042] Function of auxiliary metal salts: The addition of auxiliary metal salts such as molybdenum salts or tungsten salts can enhance the stability of the catalytic material. These auxiliary metal salts can form stable compounds with the main catalytic metals such as iron, cobalt, and nickel, thereby improving the thermal and chemical stability of the catalytic material.
[0043] Multi-step preparation process: Through multiple steps such as raw material preparation, carbon carrier pretreatment, multi-metal precursor solution preparation, impregnation reaction, reduction treatment and post-treatment, carbon-supported nano-zero-valent iron catalytic materials with high catalytic performance and stability can be gradually constructed. Each step has its specific role and purpose, which together ensure the high-quality preparation of catalytic materials.
[0044] High-performance catalytic materials: Since the catalytic materials obtained by this preparation method have high catalytic activity and stability, they can be widely used in environmental remediation, chemical catalysis and other fields. For example, in wastewater treatment, the catalytic materials can be used to accelerate the degradation of organic pollutants; in chemical production, the rate and selectivity of chemical reactions can be improved.
[0045] Embodiment 2:
[0046] The present invention provides a method for preparing a carbon-supported nanometer zero-valent iron catalytic material based on multi-metal catalysis, comprising the following steps:
[0047] Step 1: Raw material preparation
[0048] A carbon carrier is selected, and the carbon carrier is a composite of carbon nanofibers and porous graphite. The mass ratio of carbon nanofibers to porous graphite is 1:2. At least three metal salts are prepared, including iron salts as the main catalytic metal, cobalt salts and nickel salts that can promote the formation of nano zero-valent iron, and auxiliary metal salts for enhancing stability and catalytic activity, and the auxiliary metal salts are molybdenum salts or tungsten salts. The metal salts are mixed in a specific molar ratio, that is, iron salt: cobalt salt: nickel salt: auxiliary metal salt = 5:2:2:1, and the total molar concentration of the metal salts is 0.5 mol / L.
[0049] Step 2: Carbon carrier pretreatment
[0050] The carbon carrier was immersed in a solution containing a specific concentration of oxidant, the concentration of the oxidant was 0.3 mol, the immersion temperature was 60°C, and the treatment time was 4 hours. It was then washed with deionized water until neutral, and then subjected to high-temperature heat treatment in an inert atmosphere, the heat treatment temperature was 600°C, and the treatment time was 4 hours, so that the carbon carrier was activated and reached a preset surface state.
[0051] Step 3: Preparation of multi-metal precursor solution
[0052] The mixed metal salts are dissolved in a mixed solvent consisting of an organic solvent and water, wherein the organic solvent is a mixture of ethylene glycol and propylene glycol, to form a uniform multi-metal precursor solution.
[0053] Step 4: Impregnation reaction
[0054] The pretreated carbon carrier is immersed in the multi-metal precursor solution and the impregnation reaction is carried out under specific temperature and stirring conditions. The reaction temperature is 80°C, the stirring speed is 500r / min, and the reaction time is 6h, so that the metal ions are fully adsorbed on the carbon carrier.
[0055] Step 5: Restore
[0056] A reducing agent is added to the system after the impregnation reaction. The reducing agent is a mixture of sodium borohydride and sodium citrate. The reduction reaction is carried out at a certain temperature. The temperature of the reduction treatment is 50°C and the reaction time is 1h-2h. The metal ions are reduced to nano zero-valent metals and loaded on the carbon carrier to form a carbon-supported nano zero-valent iron catalytic material based on multi-metal catalysis.
[0057] Step 6: Post-processing
[0058] The product after reduction treatment is filtered and washed to remove residual reactants and impurities, and then dried at a specific temperature of 120°C and 8 hours to obtain a pure carbon-supported nano zero-valent iron catalytic material based on multi-metal catalysis.
[0059] In this embodiment, multi-metal synergistic catalysis: iron salt, cobalt salt, nickel salt are introduced as the main catalytic metals, and molybdenum salt or tungsten salt is used as the auxiliary metal salt to form a multi-metal synergistic catalytic system. The interaction between different metals can significantly improve the catalytic activity of the catalytic material and make the catalytic reaction more efficient.
[0060] Advantages of special carbon carriers: The composite of carbon nanofibers and porous graphite is used as the carbon carrier, which combines the high specific surface area of carbon nanofibers and the good stability and pore structure of porous graphite. This special carbon carrier provides more attachment sites for the loading of metal salts, which is beneficial to improve the catalytic performance of catalytic materials.
[0061] Carbon carrier pretreatment: By soaking the carbon carrier in a solution containing a specific concentration of oxidant, and then performing high-temperature heat treatment under an inert atmosphere, impurities on the surface of the carbon carrier can be removed, the surface of the carbon carrier can be activated, and its stability can be improved. At the same time, this pretreatment method can also make the bond between the carbon carrier and the metal salt more firm, and enhance the stability of the catalytic material.
[0062] Function of auxiliary metal salts: The addition of auxiliary metal salts such as molybdenum salts or tungsten salts can enhance the stability of the catalytic material. These auxiliary metal salts can form stable compounds with the main catalytic metals such as iron, cobalt, and nickel, thereby improving the thermal and chemical stability of the catalytic material.
[0063] Multi-step preparation process: Through multiple steps such as raw material preparation, carbon carrier pretreatment, multi-metal precursor solution preparation, impregnation reaction, reduction treatment and post-treatment, carbon-supported nano-zero-valent iron catalytic materials with high catalytic performance and stability can be gradually constructed. Each step has its specific role and purpose, which together ensure the high-quality preparation of catalytic materials.
[0064] High-performance catalytic materials: Since the catalytic materials obtained by this preparation method have high catalytic activity and stability, they can be widely used in environmental remediation, chemical catalysis and other fields. For example, in wastewater treatment, the catalytic materials can be used to accelerate the degradation of organic pollutants; in chemical production, the rate and selectivity of chemical reactions can be improved.
[0065] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a carbon-supported nanometer zero-valent iron catalytic material based on multi-metal catalysis, characterized in that: The following steps are involved: Step 1: Raw material preparation Selecting a carbon carrier, wherein the carbon carrier is a composite of carbon nanofibers and porous graphite; Prepare at least three metal salts, including an iron salt as a main catalytic metal, a cobalt salt and a nickel salt capable of promoting the formation of nano zero-valent iron, and an auxiliary metal salt for enhancing stability and catalytic activity, wherein the auxiliary metal salt is a molybdenum salt or a tungsten salt; the metal salts are mixed in a specific molar ratio, and the total molar concentration of the metal salts is within a specific range; Step 2: Carbon carrier pretreatment The carbon carrier is immersed in a solution containing an oxidant of a specific concentration, treated at a certain temperature for a specific time, washed with deionized water until neutral, and then subjected to a high-temperature heat treatment in an inert atmosphere to activate the carbon carrier and achieve a preset surface state; Step 3: Preparation of multi-metal precursor solution dissolving the mixed metal salts in a mixed solvent consisting of an organic solvent and water, wherein the organic solvent is a mixture of ethylene glycol and glycerol, to form a uniform multi-metal precursor solution; Step 4: Impregnation reaction The pretreated carbon carrier is immersed in a multi-metal precursor solution, and an impregnation reaction is carried out under specific temperature and stirring conditions, and the reaction time is a specific time, so that the metal ions are fully adsorbed on the carbon carrier; Step 5: Restore A reducing agent is added to the system after the impregnation reaction, wherein the reducing agent is a mixture of sodium borohydride and sodium citrate, and a reduction reaction is carried out at a certain temperature for a specific time, so that the metal ions are reduced to nano zero-valent metals and loaded on the carbon carrier, thereby forming a carbon-supported nano zero-valent iron catalytic material based on multi-metal catalysis; Step 6: Post-processing The product after the reduction treatment is filtered and washed to remove residual reactants and impurities, and then dried at a specific temperature to obtain a pure carbon-supported nano zero-valent iron catalytic material based on multi-metal catalysis.
2. The method for preparing a carbon-supported nano-zero-valent iron catalytic material based on multi-metal catalysis according to claim 1, characterized in that: In the composite of carbon nanofibers and porous graphite in step 1, the mass ratio of carbon nanofibers to porous graphite is 1:2; The molar ratio of each metal salt is iron salt: cobalt salt: nickel salt: auxiliary metal salt = 5:2:2:1; The total molar concentration of the metal salt is 0.1 mol / L-0.5 mol / L.
3. The method for preparing the carbon-supported nano zero-valent iron catalytic material based on multi-metal catalysis according to claim 1, characterized in that: In the step 2, the carbon carrier is immersed in the 0.1 mol-0.3 mol oxidant solution at a temperature of 40° C.-60° C. for a treatment time of 2 h-4 h; The high temperature heat treatment temperature under inert atmosphere is 400°C-600°C, and the treatment time is 2h-4h.
4. The method for preparing a carbon-supported nano-zero-valent iron catalytic material based on multi-metal catalysis according to claim 1, characterized in that: The temperature of the impregnation reaction in step 4 is 60° C.-80° C., the stirring speed is 200 r / min-500 r / min, and the reaction time is 4 h-6 h.
5. The method for preparing the carbon-supported nano zero-valent iron catalytic material based on multi-metal catalysis according to claim 1, characterized in that: The temperature of the reduction treatment in step 5 is 30° C.-50° C., and the reaction time is 1 h-2 h.
6. The method for preparing a carbon-supported nano-zero-valent iron catalytic material based on multi-metal catalysis according to claim 1, characterized in that: The drying temperature in the post-treatment in step six is 80° C.-120° C., and the drying time is 4 h-8 h.
Citation Information
Cited By
Preparation method of activated carbon loaded multi-metal catalyzed nano zero-valent iron deep denitrification material
CN120208393A